The Effect of Risk Perception on Anxiety in Emerging Adulthood Under the Local Outbreak of COVID-19: A Conditional Process Analysis - Fu, Haojie; Wang, Bin (Frontiers in Psychology, 2022)
This study aims to explore the influence mechanism of COVID-19 risk perception on anxiety in emerging adulthood in the context of public health events of the second round of COVID-19 outbreaks and provide support for exploring the path of mental health after the normalization of the epidemic situation. An online questionnaire, combined with community social work, was used in this study, and data of 522 emerging adults were collected in February 2021. The Perceived Risk of COVID-19 Pandemic Scale (PRCPS), the Generalized Anxiety Disorder 7-Item (GAD-7) Scale, the Scale of Affect Balance, and the Connor-Davidson Resilience Scale (CD-RISC) were used to investigate. The results showed that: first, the risk perception of COVID-19 in early adulthood was positively predictive of anxiety symptoms (B = .110, P < 0.05, 95%CI = [.042, .176]). Second, the affective quality of life plays a mediating role between the risk perception of Covid-19 and anxiety (B = .108, 95%CI = [.060, .161]). Thirdly, resilience plays a moderating role between the risk perception of Covid-19 and anxiety, the higher the resilience of emerging adulthood, the weaker effects of the risk perception of Covid-19 negative prediction of anxiety. (B = -.110, P < 0.001, 95%CI = [-.170, -.049]). Therefore, to control the anxiety of emerging adulthood in public health events, we should pay attention to the propaganda and management of epidemic information, improve the quality of life, and attention should be paid to the emerging adulthood with low resilience.